Upaya Pemerintah Desa dalam Pemberdayaan Masyarakat Melalui Usaha Air Minum Bali (Banyu Mili) Desa Paringan - Nafilah Amalia Syahida; Bambang Triono; Ekapti Wahjuni Dj; Dian Suluh Kusuma Dewi (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
The research aims to find out how the government empowers the community through the drinking water business. The method used in the research is qualitative descriptive research, with interview and documentation techniques. Data were obtained through interviews and documentation. The research locates at Paringan Village because this village is one of the villages in the district which has a drinking water business called BALI. The drinking water business was established in 2021 by utilizing natural resources which have already been existing. The establishment of the drinking water business is the effort of the government in empowering the village community. It is evidenced that the villagers work in BALI. Then, some of them work as a distributor of water which can generate income. The village government's effort is interesting to be studied. The research results that BALI can support the program of village-owned enterprises and afford to provide investment to run the development of BALI.